Perceptions and Reconstruction of Customers’ Trust of Baitul Maal wa Tamwil (BMT) in Pekalongan - Kuat Ismanto; Mohammad Nasrullah; Nalim Nalim (Faculty of Islamic Economics and Business of UIN K.H. Abdurrahman Wahid Pekalongan, 2017)
This study is aimed at investigating people’s perceptions of Baitul Maal wa Tamwil (BMT). Since its first existence, BMT has operated with full of both positive and negative dynamics. Negative perceptions and stigma are adhered to this kind of microfinance institution. Therefore, this present study is also conducted to explain well-established steps in eliminating those perceptions. For BMT, people’s trust constitutes the foremost asset to exist, particularly in the process of collecting savings from customers. This research employed a qualitative-field approach by using observation, interview, and documentation. The results of this study reveal that based on the people’s negative stigma, BMT was considered resembling a conventional financial institution applying the principle of profit sharing, in which the customers pay more. Several steps to eliminate these perceptions coped with socializing groups of people, promoting baitul maal with soft loans, carrying out a door-to-door marketing strategy, and empowering the roles of Sharia Supervisory Board (DPS).